Guidelines for the use of Unmanned Aerial Systems for fast photogrammetry-oriented mapping in emergency response scenarios. (May 2021) - Mandirola, Martina; Casarotti, Chiara; Peloso, Simone; Lanese, Igor; Brunesi, Emanuele; Senaldi, Ilaria; Risi, Federico; Monti, Alessandro; Facchetti, Carlo
Abstract: The present paper focuses on the use of Unmanned Aerial System (UAS), commonly known as drones, for the fast mapping of medium to large areas in an emergency response scenario, for example after a seismic event. The information obtained by processing the aerial acquired data (generally images) provide a significant contribution not only in supporting the Search and Rescue (SAR) activities, when timeliness is crucial, but also in the framework of debris volume assessment, exterior safety inspection of critical infrastructures and post-event reconnaissance and reconstruction activities. Within the context of coordinated flight planning for emergency aerial photogrammetry (involving the use of commercial multi-rotor UAS fleets), an operative strategy is proposed in order to address several critical aspects, frequently faced in particular when mapping large areas. The results and the lessons learned from an in-situ implementation of the presented procedure are also reported. Highlights: Survey of medium-large areas affected by catastrophes using fleets of drones. Definition of a technical-operational service in an emergency context. Photogrammetry-oriented mapping of areas affected by disasters in times compatible with emergency management. Balance between data accuracy/reliability, safety of survey and rescue teams, timeliness of result delivery. Situational awareness methodology after a major disaster.